LA NINFA Y EL NEGRO (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay shows the impossibility of the idyllic dream of Spanish domination over Cuba and shows the dilemmas of the colonial Cuban leading class, the sacarocracy, on the one hand worried about the increase in the Black population, which was necessary as labor, and also worried about the risk of political rebellion. Politics and economy stand in stark contradiction, making Arango’s autonomism non-viable.